Representation of Crime and Punishment in Selected Plays in Nigeria (2015)
Nigerian plays are replete with narration of crime and punishment as prime factor in socioeconomic conflict and resolution. Critical studies of these plays have so far focused on the views of the political class with little attention paid to the views of the masses, which are critical to the thematic engagement of the playwrights. Consequently, this study focuses attention on the views of the masses in order to expound the insights of crime and punishment in Nigeria. The study adopted Freud‟s psychoanalytic and Sartre‟s existential theories. Six plays, namely, X9yinkq‟s Death and the King’s Horseman (DKH) and The Trials of Brother Jero, (TBJ); {lq R9t8m7‟s The Gods Are Not to Blame (GANB) and K5runm7 (K); and +x-fiszn‟s Mor9unt9d6n (M) and Red is the Freedom Road (RFR) were purposely selected for their socioeconomic theme as framework in tackling issues of emotion and sensual experience. These plays were subjected to literary and critical analyses. Four views of the masses were identified in all the selected plays. These are: propaganda, deviladvocacy, chauvinism and prejudice. While propaganda and devil-advocacy were prominently evident in DKH, GANB and K, chauvinism and prejudice were the focus of TBJ, M and RFR. In DKH, evidence of propaganda and devil-advocacy is seen in the representation of the political class which sets personal interests above statutory responsibilities. Propaganda and deviladvocacy evolve from GANB obsessive illumination and focus on the failure of the political class to follow due process in addressing issues of national security. Kargues that, for every crime committed by the masses, there is always antecedence. The play draws attention to the abuse of power by the political class as an alternative explanation for crimes committed by the masses. With their focus on the objective and individualistic nature of behaviour, M, RFR and TBJ examine the existential need of the masses for self-affirmation in order to redefine their reality and existence. The plays address the need to reinforce one‟s subjective security, which overarches the issue of the criminality of an action. The pivotal roles played by emotional and sensual factors of servitude and frustration in the execution of crimes are portrayed in M and RFR. They conclude that Nigerian masses are driven to crimes by accumulated hatred towards the predatory political class. TBJ demonstrates that there are always antecedents for any crime committed by the masses. The array of thematic concerns and executions in Nigerian plays enhanced objective insights into the concepts of crime and punishment in Nigeria. The unbiased representation of these concepts projects Nigerian plays as the artistic catalysts of socio-political reordering